1999
DOI: 10.1118/1.598707
|View full text |Cite
|
Sign up to set email alerts
|

Thermal dosimetry of a focused ultrasound beam in vivo by magnetic resonance imaging

Abstract: Magnetic resonance imaging (MRI) thermometry has been utilized for in vivo evaluation of thermal exposure induced by a focused ultrasound beam. A simulation study of the focused ultrasound beam was conducted to select imaging parameters for reducing the error due to the spatial and temporal averaging of MRI. Temperature imaging based on the proton resonance frequency shift was utilized to obtain the temperature distribution during sonication in the skeletal muscle of eight rabbits. MRI-derived temperature info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
149
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(161 citation statements)
references
References 32 publications
10
149
1
1
Order By: Relevance
“…A previous study by Chung et al (35) reported that the lesion diameter computed by using TD was smaller than that measured on T2-weighted images, the latter found to be consistent with tissue damage shown in the microscopic examinations. They attributed the mismatch to the possibility that the tissue damage might continue to occur even after turning off the HIFU transmission.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A previous study by Chung et al (35) reported that the lesion diameter computed by using TD was smaller than that measured on T2-weighted images, the latter found to be consistent with tissue damage shown in the microscopic examinations. They attributed the mismatch to the possibility that the tissue damage might continue to occur even after turning off the HIFU transmission.…”
Section: Discussionsupporting
confidence: 73%
“…Whether these results could be extrapolated to the data obtained from our HIFU experiments is currently unclear due to the fundamental difference in the heating procedure. In particular on T2-weighted images alone, muscular tissues following HIFU ablation are known to exhibit rather heterogeneous distribution of the signal intensity (36), sometimes demonstrating a relative hypointense core corresponding to coagulation necrosis surrounded by a hyperintense rim of disruption vacuoles (35), unlike the findings of consistently increased intensity on T2-weighted images paralleling that on MT-weighted images after water-bath heating as reported by Graham et al (11,34). The MR signal behaviors are further complicated by strong dependence on the use of continuous wave vs. pulsed HIFU treatment (37), as well as by the dependence of histological changes on the time elapsed after the HIFU procedure (38).…”
Section: Discussionmentioning
confidence: 99%
“…While reports exist that the planned treatment volume agrees with histologically-confirmed necrotic tissue (16), there is greater evidence that this threshold is a conservative estimate (17). Studies by Chung et al (8) showed that the ablation volume was 25% larger than that planned in rabbit skeletal muscle, while a two-fold increase was shown in application to uterine fibroid treatment (B.J. Quade, personal communication, 2002).…”
Section: High-intensity Focused Ultrasound (Fus)mentioning
confidence: 93%
“…Planning is usually based on MR-derived thermal indices, in which a coagulation threshold is adopted-in most studies either a dose of 240 minutes at 43°C or a minimum peak temperature of 55°C (8,12). While reports exist that the planned treatment volume agrees with histologically-confirmed necrotic tissue (16), there is greater evidence that this threshold is a conservative estimate (17).…”
Section: High-intensity Focused Ultrasound (Fus)mentioning
confidence: 99%
“…At first, only 2D temperature maps were obtained by MRI to allow for accurate targeting of the beam (13). Later these thermal images were used to generate maps of the thermal dose (14) that could then be used to tailor the energy deposition using closed-loop feedback control (15). This preclinical work led to the development of the first commercial system by InSightec (Haifa, Israel), the Exablate 2000, the first implementation of a fully integrated MRgFUS system that combined a phased array transducer, a computer-controlled robotic positioner, and a workstation that integrated control based on MR thermometry.…”
mentioning
confidence: 99%